2020
DOI: 10.3389/fimmu.2020.00729
|View full text |Cite
|
Sign up to set email alerts
|

Rejuvenation of Neutrophil Functions in Association With Reduced Diabetes Risk Following Ten Weeks of Low-Volume High Intensity Interval Walking in Older Adults With Prediabetes – A Pilot Study

Abstract: Neutrophil dysfunction is a common feature of aging, and is associated with the pathogenesis of many age-related diseases, including type 2 diabetes mellitus (T2DM). Although exercise training improves metabolic health, decreases risk of T2DM, and is associated with improving neutrophil functions, involvement in regular physical activity declines with age. The aim of this study was to determine if neutrophil functions could be improved in association with changes in fitness and metabolic parameters in older ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 61 publications
1
52
0
Order By: Relevance
“…HIIT participants completed 99% of all prescribed exercise sessions/week and minutes/week, at a highintensity interval heart rate corresponding to 89 (2.8)% of aerobic capacity. We show a high level of compliance for achieving target heart rates that was similar to our previous HIIT studies in non-cancer populations [17,18,21]. Our study benefited from a supervised program, with high adherence and retention rates.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…HIIT participants completed 99% of all prescribed exercise sessions/week and minutes/week, at a highintensity interval heart rate corresponding to 89 (2.8)% of aerobic capacity. We show a high level of compliance for achieving target heart rates that was similar to our previous HIIT studies in non-cancer populations [17,18,21]. Our study benefited from a supervised program, with high adherence and retention rates.…”
Section: Discussionsupporting
confidence: 85%
“…We, and others, have shown that HIIT in older patients with prediabetes or rheumatoid arthritis also reduces disease burden while improving important immune functions [16][17][18][19][20]. Therefore, HIIT may be an effective form of exercise to improve physical fitness and immune functions for CLL patients.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The AUCG for cortisol remained unaffected on the first and last day of training but increased on the follow-up day with both, HIIT and LSD. sIgA secretion rate with the HIIT indicates no compromised mucosal immune function Bartlett et al (2020) Objective: Determine if neutrophil functions could be improved in association with changes in fitness and metabolic parameters in older adults at risk for Type 2 Diabetes Mellitus using 10-weeks of low volume high-intensity interval exercise training (HIIT)…”
Section: Can Exercise Intensity Compromise the Immune System?mentioning
confidence: 99%